Service Engineering European Research Results - Dustdar, Schahram; Fei Li; SpringerLink (Online service). (Vienna Springer Vienna, 2011)
Service ngineering is increasingly posing challenges to traditional software engineering methodologies including specification, modeling, architecture, and verification, just to name a few. On the other hand, the latest advancements in software engineering are continuously leveraged in Service Engineering research, especially in the design and implementation of service-oriented systems. Several mutual impacts between service engineering and software engineering could be observed in the last decade, and many research efforts have been devoted to the field. However, in spite of the considerable efforts and significant contributions, few have attempted to summarize the research results systematically.
Describing Case Studies and Classifying Research Approaches -- Modeldriven Service Engineering with SoaML.- Modelling Service Requirements Variability: The DiVA Way.- Coordination, Organisation and Model-driven Approaches for Dynamic, Flexible, Robust Software and Services Engineering.- Model-aware Monitoring of SOAs for Compliance.- Integrating Perfective and Corrective Adaptation of Service-based Applications.- Combining Domain-driven Design and Mashups for Service Development.- Guidance in Business Process Modelling.- Adaptive Service Binding with Lightweight SemanticWeb Services.- Designing and Adapting Service-based Systems: A Service Discovery Frame Work.- VRESCo Vienna Runtime Environment for Service-oriented Computing -- Glossary -- Index.
Electronic reproduction.
Keywords: Service-oriented architecture (Computer science); Electronic book